2020
DOI: 10.1002/jat.4106
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to mono (2‐ethylhexyl) phthalate facilitates apoptosis and pyroptosis of human endometrial microvascular endothelial cells through NLRP3 inflammasome

Abstract: Mono (2‐ethylhexyl) phthalate (MEHP) is a major metabolite of di (2‐ethylhexyl) phthalate (DEHP). This study aimed to observe the toxic effect of MEHP on human endometrial microvascular endothelial cells (HEMECs) and its potential molecular mechanism. HEMECs were exposed to different concentrations of MEHP (0, 50, 100, and 200 nM). Cell viability and apoptosis were assessed by cell counting kit‐8 (CCK‐8) and flow cytometry assays. Western blot was performed to examine the expression of apoptosis‐related protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 32 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Increased NLRP3, AIM and P2xR7 expression and increased secretion of active p20kD Caspase-1 and p17kD IL-1β was found in THP-1 monocytes exposed to doses of DEHP expected post-surgery. Consistently, DEHP, its metabolite MEHP and di-butyl phthalate have activated NLRP3 and increased Il-1β secretion in human and rat monocyte cell lines [ 33 36 ] as well as other cell lines [ 71 74 ]. In contrast, increases in pattern recognition receptor or effector expression were not detected with TOTM, DOS or DHPS exposure in THP-1 cells suggesting that these chemicals do not induce substantial inflammasome activation in macrophages.…”
Section: Discussionmentioning
confidence: 96%
“…Increased NLRP3, AIM and P2xR7 expression and increased secretion of active p20kD Caspase-1 and p17kD IL-1β was found in THP-1 monocytes exposed to doses of DEHP expected post-surgery. Consistently, DEHP, its metabolite MEHP and di-butyl phthalate have activated NLRP3 and increased Il-1β secretion in human and rat monocyte cell lines [ 33 36 ] as well as other cell lines [ 71 74 ]. In contrast, increases in pattern recognition receptor or effector expression were not detected with TOTM, DOS or DHPS exposure in THP-1 cells suggesting that these chemicals do not induce substantial inflammasome activation in macrophages.…”
Section: Discussionmentioning
confidence: 96%
“…An showed that mono (2‐ethylhexyl) phthalate (MEHP), a major metabolite of di (2‐ethylhexyl) phthalate (DEHP), induced apoptosis and pyroptosis of human endometrial microvascular endothelial cells (HEMECs). The cytotoxicity of MEHP is related with NLRP3 inflammasome, and knock‐down of NLRP3 ameliorated the cytotoxicity of MEHP (An, 2020). Liang et al showed that exposure to cadmium (Cd) induced cytotoxicity to human microvascular endothelial cells (HMEC‐1).…”
mentioning
confidence: 99%